Blended learning for generation alpha during the COVID-19 pandemic - Wirawati Ngui Yi Xe; Mohd. Zaki Ishak; Crispina Gregory K. Han; Tan Choon Keong; Haridah Utu Satu (Human Resource Management Academic Research Society, 2023)
The COVID-19 pandemic accelerated the integration of online learning in the secondary education context in an unprecedented manner. Teachers who were accustomed to conducting lessons fully in the classroom had to search for various technology-based alternatives to replace the conventional form of teaching and learning. The purpose of this study was to explore the blending of online and physical learning, also known as “blended learning”, across government secondary schools throughout the COVID-19 pandemic. This is a qualitative study that involved 58 secondary school teachers from 3 districts in Sabah, Malaysia. Focus group interviews were employed to gather data about the use of blended learning among teachers in the districts of Tawau, Kota Kinabalu and Keningau. The data were analysed using thematic analysis. The findings showed that the participants used a variety of online learning applications to deliver content, to provide social and emotional support to the learners and learners’ parents, and to evaluate learner performance. The findings also revealed that in some cases, the teachers had to create physical learning materials for the students. This study revealed the various ways teachers blended online and face-to-face approaches to cater to their learners. The outcomes are valuable for pre-service and inservice teachers who are keen to employ blended learning in the 21st century classroom.